Detection of CTNNB1 Hotspot Mutations in Cell-Free DNA from the Urine of Hepatocellular Carcinoma Patients - Selena Y. Lin; Ting-Tsung Chang; Jamin D. Steffen; Sitong Chen; Surbhi Jain; Wei Song; Yih-Jyh Lin; Ying-Hsiu Su (Diagnostics, 2021)
Hepatocellular carcinoma (HCC) is a leading cause of cancer-related deaths worldwide. The beta-catenin gene, CTNNB1, is among the most frequently mutated in HCC tissues. However, mutational analysis of HCC tumors is hampered by the difficulty of obtaining tissue samples using traditional biopsy. Here, we explored the feasibility of detecting tumor-derived CTNNB1 mutations in cell-free DNA (cfDNA) extracted from the urine of HCC patients. Using a short amplicon qPCR assay targeting HCC mutational hotspot CTNNB1 codons 32–37 (exon 3), we detected CTNNB1 mutations in 25% (18/73) of HCC tissues and 24% (15/62) of pre-operative HCC urine samples in two independent cohorts. Among the CTNNB1-mutation-positive patients with available matched pre- and post-operative urine (n = 13), nine showed apparent elimination (n = 7) or severalfold reduction (n = 2) of the mutation in urine following tumor resection. Four of the seven patients with no detectable mutations in postoperative urine remained recurrence-free within five years after surgery. In contrast, all six patients with mutation-positive in post-operative urine recurred, including the two with reduced mutation levels. This is the first report of association between the presence of CTNNB1 mutations in pre- and post-operative urine cfDNA and HCC recurrence with implications for minimum residual disease detection.